1981
DOI: 10.1523/jneurosci.01-05-00461.1981
|View full text |Cite
|
Sign up to set email alerts
|

The loss of neuron-specific proteins during the course of Wallerian degeneration of optic and sciatic nerve

Abstract: To identify axonal proteins which are unique constituents of neurons, the spectrum of detectable proteins of degenerating nerves has been compared with that of intact control nerves from the same animals. Wallerian degeneration was induced in rabbits by unilateral transection of the optic and sciatic nerves. Proteins of nerve homogenates were compared by sodium dodecyl sulfate-gel electrophoresis and by two-dimensional electrophoresis. Four non-myelin proteins disappear from degenerating nerve. These include t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…The biological consequence of the binding of intermediate filament subunits to the 66-kD protein might be to organize them into a cytoskeletal framework. In this regard, it is interesting that Soifer et al (29) observed the disappearance of a 65-kD polypeptide, with an isoelectric point similar to that determined for the 66-kD protein, coincident with the disappearance of the three neurofilament triplet proteins, from both optic and sciatic nerves undergoing Wallerian degeneration. Further studies on the appearance of this protein during development and various disease states may give us further clues as to its importance in both Wallerian degeneration and cytoskeletal dissolution, as well as in growth and cytoskeletal organization.…”
Section: Discussionmentioning
confidence: 64%
“…The biological consequence of the binding of intermediate filament subunits to the 66-kD protein might be to organize them into a cytoskeletal framework. In this regard, it is interesting that Soifer et al (29) observed the disappearance of a 65-kD polypeptide, with an isoelectric point similar to that determined for the 66-kD protein, coincident with the disappearance of the three neurofilament triplet proteins, from both optic and sciatic nerves undergoing Wallerian degeneration. Further studies on the appearance of this protein during development and various disease states may give us further clues as to its importance in both Wallerian degeneration and cytoskeletal dissolution, as well as in growth and cytoskeletal organization.…”
Section: Discussionmentioning
confidence: 64%
“…The great abundance of these proteins in the optic nerve suggests that they may be important structural proteins of axons or glia; some of them may be neurofilament proteins or nonneuronal intermediate filament proteins Schechter, 1983a, 1984). Like neurofilament proteins (Hoffman and Lasek, 1980;Dahl et al, 1981;Soifer et al, 1981), ON1 and ON2 were rapidly lost from the degenerating nerve. The time course of their reappearance would be consistent with an increase in neurofilaments accompanying the recovery in axonal diameter which is in progress by 12 weeks after nerve crush (Murray, 1982).…”
Section: Discus Stonmentioning
confidence: 99%
“…This possibility seemed all the more compelling in view of the recent report (Drgtger et al 1983) that neurofilament protein contains an immunologically-recognised ct-MSH-like portion. This protein has been shown to break down in the early stages of the degenerative process (Bignami et al 1981 ;Soifer et al 1981). We therefore investigated the possible presence of an ~-MSHlike principle in the degenerating nerves during the period of 150 kD neurofilament protein breakdown and ct-MSH sensitivity.…”
Section: Introductionmentioning
confidence: 99%